2012
DOI: 10.1504/ijlc.2012.045857
|View full text |Cite
|
Sign up to set email alerts
|

The BGR contingency model for leading change

Abstract: The continuing failure rates of change initiatives, combined with an increasingly complex business environment, have created significant challenges for the practice of change management. High failure rates suggest that existing change models are not working, or are being incorrectly used. A different mindset to change is required. The BGR Contingency Model (named after the authors' surnames) for leading change facilitates the required mindset, and addresses the issue of leadership decision-making as one of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…The Framework, shown in Figure 1, was originally designed as a change management model (Brown et al, 2012). Experience in applying the model, however, demonstrated that it is equally effective as a leadership decision-making framework.…”
Section: A Leadership Decision-making Frameworkmentioning
confidence: 99%
“…The Framework, shown in Figure 1, was originally designed as a change management model (Brown et al, 2012). Experience in applying the model, however, demonstrated that it is equally effective as a leadership decision-making framework.…”
Section: A Leadership Decision-making Frameworkmentioning
confidence: 99%